2008
DOI: 10.1002/da.20401
|View full text |Cite
|
Sign up to set email alerts
|

Reexamination of the MASC factor structure and discriminant ability in a mixed clinical outpatient sample

Abstract: Anxiety problems in youth are common, suggesting the need for developmentally appropriate and psychometrically sound measures in this area. The Multidimensional Anxiety Scale for Children (MASC) was created with this goal in mind, but has yet to be examined with samples representative of youth typically seen in clinical settings. Two hundred and sixty-two outpatient youth with mixed clinical presentations completed the MASC, a measure that includes a total anxiety score, as well as subscale scores for social a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 21 publications
3
43
1
1
Order By: Relevance
“…This instrument provides reliable and valid assessments of anxiety symptoms, discriminates between important anxiety symptoms, and is sensitive to treatment-induced changes in symptoms [23]. Acceptable reliability and validity have been shown in epidemiological, school, and clinical samples [23][24][25]. Internal consistency was adequate in this study: MASC Total (a = .93), Physical Symptoms (a = .93), Harm Avoidance (a = .85), Social Anxiety (a = .87), and Separation Anxiety (a = .71).…”
Section: Multidimensional Anxiety Scale For Children [23]mentioning
confidence: 99%
“…This instrument provides reliable and valid assessments of anxiety symptoms, discriminates between important anxiety symptoms, and is sensitive to treatment-induced changes in symptoms [23]. Acceptable reliability and validity have been shown in epidemiological, school, and clinical samples [23][24][25]. Internal consistency was adequate in this study: MASC Total (a = .93), Physical Symptoms (a = .93), Harm Avoidance (a = .85), Social Anxiety (a = .87), and Separation Anxiety (a = .71).…”
Section: Multidimensional Anxiety Scale For Children [23]mentioning
confidence: 99%
“…The four-factor structure of the MASC has been consistently supported in both community and clinical samples in the United States [13][14][15][16], as well as in Icelandic schoolchildren [17], Swedish adolescents [18], Australian children [9], and South African adolescents [19]. Meanwhile, research found that the MASC has good test-retest reliability [15], internal consistency [10,[14][15][16], convergent validity [16,20], and discriminant validity [16,21].…”
Section: Introductionmentioning
confidence: 97%
“…Second, the study of Yao and colleagues [23] did not examine the psychometrics of the MASC in Chinese adolescents below the age of 14 years. Third, to date, only a few studies have explored the discriminant validity of the MASC and the results are inconsistent [13]. For instance, March [12] and Rynn et al [16] reported good discriminant ability, whereas van Gastel and Ferdinand [25] reported more variable findings.…”
Section: Introductionmentioning
confidence: 97%
“…Vários estudos com populações gerais e com populações clínicas apoiaram a sua consistência interna, estabilidade temporal e validade convergente (GrillsTaquechel, Ollendick, & Fisak, 2008;Kingery, Ginsburg, & Burstein, 2009;March et al, 1997;Ólason, Sighvatsson, & Smári, 2004;Rynn et al, 2006;Villabø, Gere, Torgersen, March, & Kendall, 2012), pelo que a MASC representou um avanço na avaliação da ansiedade em crianças e adolescentes, pela sua estrutura fatorial hierárquica e forte validade divergente e discriminante. Nomeadamente, a forte validade divergente da MASC ofereceu uma vantagem significativa na avaliação da ansiedade infantil na prática clínica, ao discriminar entre construtos diagnósticos.…”
Section: Introductionunclassified